The Effect of Corporate Risk Governance on the Intention of New Employee to Engage in Risk-informed Behavior (A Case Study of An Indonesian Heavy Equipment Company) - Luh Devany (Journal of Innovative and Creativity, 2026)
To support internal control and promote risk aware behavior, Audit and Risk Management practices are essential to understand especially in high risk industries. As part of Corporate risk governance, these practices can be introduced through orientation programs for new employees. However, evidence on their behavioral impact remains limited in the Indonesian heavy equipment context. This study illustrates the effect of Audit and Risk Management Orientation (ARO) as part of Corporate Risk Governance on new employees’ behavioral intention using the Theory of Planned Behavior (TPB). Data were collected from 50 new employees (≤ 12 months tenure) through a questionnaire and analyzed using PLS-SEM. The results show that ARO signifiantly influences attitudes toward risk-aware behavior but does not affect subjective norms or perceived behavioral control. Instead, perceived behavioral control comes as the strongest predictor of intention. Mediation analysis indicates that TPB variables do not mediate the relationship between ARO and behavioral intention. These findings highlight the need to complement orientation with practical experience and ongoing support.